One or two dose regimen of the SARS-CoV-2 synthetic DNA vaccine INO-4800 protects against respiratory tract disease burden in nonhuman primate challenge model. Issue 34 (9th August 2021) - Gooch, Karen E.; Smith, Trevor R.F.; Salguero, Francisco J.; Fotheringham, Susan A.; Watson, Robert J.; Dennis, Mike J.; Handley, Alastair; Humphries, Holly E.; Longet, Stephanie; Tipton, Tom; Sarfas, Charlotte; Sibley, Laura; et al.
Abstract: Safe and effective vaccines will provide essential medical countermeasures to tackle the COVID-19 pandemic. Here, we assessed the safety, immunogenicity and efficacy of the intradermal delivery of INO-4800, a synthetic DNA vaccine candidate encoding the SARS-CoV-2 spike protein in the rhesus macaque model. Single and 2 dose vaccination regimens were evaluated. Vaccination induced both binding and neutralizing antibodies, along with IFN-γ-producing T cells against SARS-CoV-2. Upon administration of a high viral dose (5 × 10 6 pfu) via the intranasal and intratracheal routes we observed significantly reduced virus load in the lung and throat, in the vaccinated animals compared to controls. 2 doses of INO-4800 was associated with more robust vaccine-induced immune responses and improved viral protection. Importantly, histopathological examination of lung tissue provided no indication of vaccine-enhanced disease following SARS-CoV-2 challenge in INO-4800 immunized animals. This vaccine candidate is currently under clinical evaluation as a 2 dose regimen.